Wireless electric board based on an ARM-based embedded system - Di Wu; Yang Zhang; Baoding Zhou (2010 3rd IEEE International Conference on Computer Science and Information Technology, 2010)
Using chalk is not only laborious, but it also produces a lot of chalk dust, polluting the air and adversely affecting the health of the students and teachers. This design uses ARM9 board for hand-held terminal hardware and uC/OS-II embedded real time operating system for hand-held terminal software. When teacher writes on a book-size touch screen with an electrical pen, handwriting signal will be converted to electrical signal and transferred to the PC terminal software by nRF2401 wireless transmission module in the band of frequency 2.4GHz. Then the PC terminal software will process the handwriting signal and display it in a larger form by projector.